Impacts of doctor-shopping behavior on diabetic patients' health: A retrospective longitudinal study in Taiwan. Issue 32 (7th August 2020) - Lin, Chin-Shien; Khan, Haider; Chang, Ruei-Yuan; Liao, Wei-Chih; Chen, Yi-Hsin; Huang, Bo-Lin; Hsieh, Teng-Fu
Abstract : Abstract: The aim of this study was to clarify the relationship between doctor-shopping behavior and clinical conditions, and to clearly outline the effects of both the number of clinic visits and the number of doctor changes on patients' health conditions. Data from January 1, 2000 to December 31, 2004 was collected from the National Health Insurance Research Database in Taiwan. After randomly selecting one million people, we extracted 5-year longitudinal data, about the number of clinic visits, number of doctor changes, and changes in self-health status for each patient with diabetes over the age of 18. We developed a relationship among the variables by using the generalized estimating equation. The results revealed that the number of clinic visits on the change of health status is a U curve, suggesting that health condition could be optimal with an appropriate number of clinic visits. The effect of the number of doctor changes is linearly correlated with health deterioration. The results suggest that disease conditions can only be controlled with an adequate number of clinic visits. Excessively frequent clinic visits are not only unfavorable to patients' health status but are also wasteful of limited medical resources. For diabetic mellitus patients, the more they change doctors, the worse their health status. All of these results are important for patients to stay healthy and to save medical resources.